Gemtuzumab ozogamicin plus midostaurin in combination with standard ‘7 + 3’ induction therapy in newly diagnosed AML: results from the SAL-MODULE phase I study - Röllig, Christoph; Schliemann, Christoph; Ruhnke, Leo; Fransecky, Lars; Heydrich, Björn-Niklas; Hanoun, Maher; Noppeney, Richard; Schäfer-Eckart, Kerstin; Wendelin, Knut; Mikesch, Jan-Henrik; Middeke, Jan Moritz; Reimann, Manja; et al. (British journal of haematology, 2024)
We conducted a phase I trial in newly diagnosed acute myeloid leukaemia (AML) to investigate the combination of two novel targeted agents, gemtuzumab ozogamicin (GO) and midostaurin, with intensive chemotherapy in FLT3-mutated AML and CBF leukaemia. Three dose levels of midostaurin and one to three sequential doses of 3 mg/m2 GO in combination with ‘7 + 3’ induction were evaluated. Based on safety findings in 12 patients, our results show that 3 mg/m2 GO on Days 1 + 4 and 100 mg midostaurin on Days 8-21 can be safely combined with IC in newly diagnosed AML.